Dampak Kerusakan Lingkungan Akibat Eksploitasi Sumber Daya Mineral dari Kegiatan Pertambangan - Mawardi Heru Prasetyo; Dewi Wahyuni K. Baderan; Marini Susanti Hamidu (Hidroponik : Jurnal Ilmu Pertanian Dan Teknologi Dalam Ilmu Tanaman, 2025)
Exploitation of mineral resources through mining activities in Indonesia provides significant economic benefits, but also causes various negative impacts on the environment and socio-economic life of local communities. This study aims to review the impacts of various types of mining activities such as sand, coal, and gold. Common environmental damages include deforestation, soil erosion, water, soil, and air pollution, and decreased biodiversity. Socio-economically, mining increases social conflict, health problems, and changes in people's livelihoods. Effective management efforts include law enforcement against illegal activities, implementation of reclamation and rehabilitation, application of impact mitigation technology, and active involvement of local communities in environmental management. Consistent implementation of policies and mitigation measures is key to achieving a balance between economic benefits and environmental sustainability.